SUSU FERMENTASI DENGAN BIJI NANGKA SEBAGAI PREBIOTIK - Winiati P. Rahayu; Suliantari Suliantari; Umi Kartika Safitri; Wibisono Adhi (Jurnal Teknologi dan Industri Pangan, 2020)
Jackfruit seeds (Artocarpus heterophyllus Lam.) contain dietary fiber, thus it is potential as prebiotic to be used in fermented milk drink. This research aimed to obtain the fermented milk composition made from fresh milk and jackfruit seed flour containing active lactic acid bacteria (LAB), preferred hedonic level and to identify the chemical properties of the resulting fermented milk. Variables of this research were the jackfruit seed flour concentrations of 4, 5, 6% (w/v) and two LAB used (Lactobacillus plantarum and Lactobacillus brevis). The composition was selected based on the viable number of LAB, pH value, and sensory quality. The selected composition was the fermented milk made of fresh milk and 4% (w/v) jackfruit seed flour and L. brevis. The viable number of LAB of the fermented milk was 10.59 log CFU/mL. The sensory quality of the fermented milk was neutral until rather preferred for color, flavor, taste, texture, and overall. The chemical contents (%b/b) of product was 78.16% of moisture content, 2.34% of ash content, 2.85% of fat content, 3.15% of protein content, 13.51% of carbohydrate content, and 1.73% of lactic acid content.